1978
DOI: 10.1128/aem.36.2.252-256.1978
|View full text |Cite
|
Sign up to set email alerts
|

Fungal contamination and mycotoxin detection of powdered herbal drugs

Abstract: Forty-nine powdered herbal drugs were analyzed for their mold profile and for the potential presence of three mycotoxins (aflatoxin, sterigmatocystin, ochratoxin A). Aspergillus and Penicillium species were predominant, but Rhizopus, Mucor, Cladosporium, and Aureobasidium spp. were also found in a few samples. Mycotoxins were not detected in any samples, and only one isolated culture was found to be a mycotoxin producer on laboratory media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(22 citation statements)
references
References 4 publications
1
20
0
1
Order By: Relevance
“…For example, AFs were not found in any of cinnamon powder samples (n=17) in spices marketed in Turkey (Ozbey and Kabak, 2012). AFs were also not detected in cinnamon powder samples marketed in Japan (Hitokoto et al, 1978), India (Saxena and Mehrotra, 1989), Bahrain (Musaiger et al, 2008), Korea (Cho et al, 2008) and Ireland (O'Riordan and Wilkinson, 2008). These results indicate that cinnamon is likely not to be a good substrate for growth of mycotoxin-producing fungi and mycotoxin accumulation.…”
Section: Aflatoxins Content In Spicesmentioning
confidence: 99%
“…For example, AFs were not found in any of cinnamon powder samples (n=17) in spices marketed in Turkey (Ozbey and Kabak, 2012). AFs were also not detected in cinnamon powder samples marketed in Japan (Hitokoto et al, 1978), India (Saxena and Mehrotra, 1989), Bahrain (Musaiger et al, 2008), Korea (Cho et al, 2008) and Ireland (O'Riordan and Wilkinson, 2008). These results indicate that cinnamon is likely not to be a good substrate for growth of mycotoxin-producing fungi and mycotoxin accumulation.…”
Section: Aflatoxins Content In Spicesmentioning
confidence: 99%
“…The obtained results in this study were in correspondence with our previous reports (Darwish, 2016a;Darwish et al, 2016b;Darwish et al, 2014a). The incidence of meat contamination with different mould genera was investigated in different localities of the world such as Australia, Japan, Italy and Spain (Hitokoto et al, 1978;Iacumin et al, 2009;King et al, 1986;Martin-Sanchez et al, 2011)). Fungal contamination of meat may lead to their spoilage and production of mycotoxins with potential health hazards to human due to their carcinogenic effects, liver diseases and organ damage (Darwish et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Manganese (Mn), mercury (Hg), and arsenic (As), in some of the most commonly used medicinal plants. The results of these studies showed that metals like Lead , Cadmium, Aluminum, Mercury and arsenic in the tested plants were above the set standard [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 94%